COUNTERFORCE ORTHOSIS IN THE MANAGEMENT OF LATERAL EPICONDYLITIS - Vellilappily, Daison Varghese; Rai, Heroor Ravindranath; Varghese, Jaison; Renjith, Vishnu (Journal of Ayub Medical College Abbottabad, 2017)
Background: Lateral Epicondylitis (LE), is a condition characterized by the pain and tenderness over the lateral epicondyle of the humerus. LE is commonly seen among people who are involved in sports such as tennis and golf. Any activity that repeatedly overstrain the extensor carpi radialis brevis tendon can lead to LE. The management of lateral epicondylitis generally involves the use of counterforce orthosis. The aim of this review is to summarize the evidence regarding the effectiveness of counterforce orthoses on the clinical outcomes of patients with lateral epicondylitis. Methods: The PubMed, Ovid, and ProQuest databases were searched for potential studies which explored the use of counterforce orthosis in the management of lateral epicondylitis Results: To have a better understanding of the effectiveness of various types of orthoses, the review is organized into four sections. The first section explores the use of a single orthotic device, the second section focuses on the combined use of orthotic devices, the third section explore studies that compared the effect of local steroid injection along with orthosis and the last section narrate the studies that compared various types of orthotic devices. The studies support the use of orthotic devices as a treatment modality for lateral epicondylitis. There is rising evidence which supports the use of a comprehensive approach, (by combining routine physiotherapy with orthotic devices) in the management of LE. Conclusion: Orthosis alone or in combination with routine physical therapy can be considered as an evidence-based treatment strategy for patients with lateral epicondylitis. However, on the basis of the literature review conducted, the authors recommend that further high-quality clinical trials regarding the management of lateral epicondylitis are necessary to strengthen the evidence-based physiotherapy practice. Keywords: Lateral Epicondylitis; Tennis Elbow; Counterforce Orthosis; Narrative Review; Literature Review